Field guide to Ethiopian orchids - Cribb, Phillip James 1946-; Rasmussen, Finn N. 1938- (UK : Royal Botanic Gardens, Kew, 2004)
Ethiopia's orchids are sparsely represented in herbaria and their biology, ecology and conservation status remains poorly understood. Written by leading orchid specialists, and with detailed descriptions, keys, line drawings, distribution maps and colour photographs, this new field guide will be an invaluable identification tool, providing urgently needed help in clarifying the status of these wonderfully diverse plants, many of which are rare or endangered.